2005
DOI: 10.1002/adma.200400368
|View full text |Cite
|
Sign up to set email alerts
|

Fully Transparent ZnO Thin‐Film Transistor Produced at Room Temperature

Abstract: Functional oxide materials currently represent a key challenge as well as a promising powerful tool for both fundamental understanding and technological development of the next generation of transparent electronics, such as field-effect transistors.[1] Here, we report a fully transparent ZnO thin-film transistor (ZnO-TFT) with a transmittance above 80 % in the visible part of the spectrum, including the glass substrate, fabricated by radiofrequency (rf) magnetron sputtering at room temperature, with a bottom g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
422
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 811 publications
(428 citation statements)
references
References 11 publications
4
422
2
Order By: Relevance
“…To date, most metal oxide TFTs have been fabricated with amorphous indium zinc oxide (α-IZO), zinc indium tin oxide, 8 ZnO,9 In 2 O 3 , 7 indium gallium zinc oxide, 10−12 or some other oxide semiconductors as channel materials by the sol−gel route, with the performance approaching that of crystalline silicon based materials.…”
mentioning
confidence: 99%
“…To date, most metal oxide TFTs have been fabricated with amorphous indium zinc oxide (α-IZO), zinc indium tin oxide, 8 ZnO,9 In 2 O 3 , 7 indium gallium zinc oxide, 10−12 or some other oxide semiconductors as channel materials by the sol−gel route, with the performance approaching that of crystalline silicon based materials.…”
mentioning
confidence: 99%
“…As shown in Fig. 3(a) and (b), Fortunato et al [20] reported room temperature fabricated ZnO TFTs with invert-staggered structure (high mobility value: approximately 50 cm 2 /V · s) by carefully optimizing oxygen partial pressure during ZnO growth. In fact, the control of oxygen partial pressure suggested a path to the fabrication of highly efficient and reliable TFTs, opening new doors towards the realization of transparent electronic circuits.…”
Section: Operation Of the Tfts And Important Device Parametersmentioning
confidence: 99%
“…After publication of these results, many ZnO TFTs were reported with improved performance and with lowered deposition temperatures suitable for flexible and transparent electronics applications [20][21][22][23]. As shown in Fig.…”
Section: Operation Of the Tfts And Important Device Parametersmentioning
confidence: 99%
“…On the other hand, metal-oxide semiconductor TFTs that can be processed at low temperatures and yield high mobility values, with a few exceptions, 3 operate mainly as n-channel TFTs. 2,4 Metal-oxide TFTs that are stable under continuous bias stress typically require annealing at temperatures higher than 300 o C, however, strategies are emerging to reduce its processing temperatures, making them more suitable to flexible substrates. 5,6 Therefore, n-channel metal-oxide TFTs combined with p-channel organic TFTs could be used to realize complementary circuit designs that benefit from the intrinsic advantages of these two classes of semiconductors.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%